Amino functionalized silica nanoparticles incorporated thin film nanocomposite membrane with suppressed aggregation and high desalination performance. (10th October 2018) - Abadikhah, Hamidreza; Kalali, Ehsan Naderi; Behzadi, Shabnam; Khan, Sayed Ali; Xu, Xin; Agathopoulos, Simeon
Abstract: Novel thin film composite (TFC) and nanocomposite (TFN) membranes were fabricated by in-situ interfacial polymerization of m -phenylenediamine aqueous solution and 1, 3, 5-benzenetricarbonyltrichloride organic solution on polyethersulfone/silicon nitride composite hollow fiber substrate. Amino functionalization of silica nanoparticles (SNPs) by p -aminophenol can improve the compatibility of SNPs with polyamide active layer, and decrease the formation of agglomerates during the interfacial polymerization, enabling, therefore, the successful fabrication of high quality TFN membranes. Uniform p -aminophenol functionalized SNPs (MSNPs) dispersion into the polyamide layer was achieved by molecular interaction and covalent bonds formation between the nanoparticles and the polyamide matrix. The hydrophilicity of TFN is significantly improved by incorporating MSNPs, which is attributed to the presence of hydrophilic amine groups (NH2 ) on the surface of the modified nanoparticles. The TFN membranes considerably enhanced the permeate flux, compared to the TFC membrane, and their salt (MgSO4 ) rejection was higher than 95%. Graphical abstract: Highlights: TFN membrane was fabricated on PES/Si3 N4 composite hollow fiber substrate. Robust asymmetric Si3 N4 microfilter acted as an excellent substrate for TFC. p-aminophenol was successfully used for silica nanoparticles amino functionalization. Functionalized nanoparticles improved hydrophilicity of TFN membranes. Desalination efficiency was increased by functionalized nanoparticles incorporation.